2009
DOI: 10.1016/j.ophtha.2009.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Artery OcclusionAssociated Systemic and Ophthalmic Abnormalities

Abstract: Objective-To investigate systematically the various associated systemic and ophthalmic abnormalities in different types of retinal artery occlusion (RAO). Design-Cohort study.Participants-439 consecutive untreated patients (499 eyes) with RAO, first seen in our clinic from 1973 to 2000.Methods-At first visit, all patients had a detailed ophthalmic and medical history, and comprehensive ophthalmic evaluation. Visual evaluation was done by recording visual acuity, using the Snellen visual acuity chart, and visua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
372
3
30

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 337 publications
(422 citation statements)
references
References 39 publications
17
372
3
30
Order By: Relevance
“…64 Hayreh et al 20 showed no cause-effect relationship between CRAO and ocular neovascularization in their cohort of 232 patients with CRAO. 20 On the other hand, Rudkin et al 64 showed a temporal relationship between the CRAO and neovascularization events, and the patients who developed neovascularization did not have other clinical features, such as diabetes or an association with a haemodynamically significant stenosis of the carotid artery to account for the neovascularization other than CRAO. As such, there is no consensus on the best followup regimen after CRAO to detect the ocular neovascular complications and optimally manage CRAO.…”
Section: (B) Preventing Ocular Neovascularization Complication In Thementioning
confidence: 89%
See 1 more Smart Citation
“…64 Hayreh et al 20 showed no cause-effect relationship between CRAO and ocular neovascularization in their cohort of 232 patients with CRAO. 20 On the other hand, Rudkin et al 64 showed a temporal relationship between the CRAO and neovascularization events, and the patients who developed neovascularization did not have other clinical features, such as diabetes or an association with a haemodynamically significant stenosis of the carotid artery to account for the neovascularization other than CRAO. As such, there is no consensus on the best followup regimen after CRAO to detect the ocular neovascular complications and optimally manage CRAO.…”
Section: (B) Preventing Ocular Neovascularization Complication In Thementioning
confidence: 89%
“…A recent aged-matched cohort study, including 249 patients (289 eyes) with CRAO, confirms these associations with the addition of renal disease. 20 Other risk factors are a family history of any type of vascular disease. In younger patients (under 50 years), proatherogenic states, such as hyperhomocystenemia, factor V Leiden, protein C and S and anti-thrombin deficiencies, anti-phospholipid antibodies or prothrombin gene mutations, sickle cell disease, and migraine due to vasospasm and paraneoplastic syndromes may all contribute to non-arteritic CRAO.…”
Section: Anatomy and Pathophysiologymentioning
confidence: 99%
“…Microemboli may be derived from non-hemodynamically significant obstruction, due to only a small intraluminal plaque(s), most commonly from carotid arteries (66%), which may be present even in absence of significant stenosis of carotid artery. 84 Arterial hypertension, diabetes mellitus, hyperlipidemia, carotid artery disease, coronary artery disease, transient ischemic attack and tobacco smoking are the common risk factors for retinal arterial occlusions, with systemic hypertension showing a significant association in more than 50% of these patients. 84 Echocardiographic abnormalities have been documented in patients with RAO with 10% needing systemic management.…”
Section: Other Eye Conditions Associated With Hypertensionmentioning
confidence: 99%
“…84 Arterial hypertension, diabetes mellitus, hyperlipidemia, carotid artery disease, coronary artery disease, transient ischemic attack and tobacco smoking are the common risk factors for retinal arterial occlusions, with systemic hypertension showing a significant association in more than 50% of these patients. 84 Echocardiographic abnormalities have been documented in patients with RAO with 10% needing systemic management. 81 RAO has also been reported to be associated with an increase risk of cardiovascular disease, stroke and mortality.…”
Section: Other Eye Conditions Associated With Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation